Marine and coastal ecosystem services on the science–policy–practice nexus: challenges and opportunities from 11 European case studies. Issue 3 (29th November 2017) - Drakou, Evangelia G.; Kermagoret, Charlène; Liquete, Camino; Ruiz-Frau, Ana; Burkhard, Kremena; Lillebø, Ana I.; van Oudenhoven, Alexander P. E.; Ballé-Béganton, Johanna; Rodrigues, João Garcia; Nieminen, Emmi; Oinonen, Soile; Ziemba, Alex; et al.
ABSTRACT: We compared and contrasted 11 European case studies to identify challenges and opportunities toward the operationalization of marine and coastal ecosystem service (MCES) assessments in Europe. This work is the output of a panel convened by the Marine Working Group of the Ecosystem Services Partnership in September 2016. The MCES assessments were used to (1) address multiple policy objectives simultaneously, (2) interpret EU-wide policies to smaller scales and (3) inform local decision-making. Most of the studies did inform decision makers, but only in a few cases, the outputs were applied or informed decision-making. Significant limitations among the 11 assessments were the absence of shared understanding of the ES concept, data and knowledge gaps, difficulties in accounting for marine social–ecological systems complexity and partial stakeholder involvement. The findings of the expert panel call for continuous involvement of MCES 'end users', integrated knowledge on marine social–ecological systems, defining thresholds to MCES use and raising awareness to the general public. Such improvements at the intersection of science, policy and practice are essential starting points toward building a stronger science foundation supporting management of European marine ecosystems.EDITED BY Sebastian Villasante